BESUS ASRI: KEBIJAKAN LINGKUNGAN BERBASIS KOMUNITAS PENGELOLAAN SAMPAH RUMAH TANGGA - Hawawi, Alfina (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This research discusses the implementation of community-based environmental policies in managing household waste through the Besus Asri community. This research uses a qualitative method that examines community-based environmental policies for waste management to improve community quality and sustainable development. The data in this research was collected through observation, interviews and documentation involving members of the Besus Asri community. By using the basis of Max Weber's social structure theory in analyzing the findings obtained by researchers. The results of this research show that the success of the program is very dependent on the role of local authorities in providing direction, as well as the formation of social norms or rules that support environmental care behavior. Apart from that, the community's contribution to this program is reflected in social interactions between individuals and groups. In this way, the Besus Asri community is not only a waste management agent, but also shows how social structure influences the success of community-based environmental policies consisting of housewives.